2012
DOI: 10.1007/s11434-012-5077-3
|View full text |Cite
|
Sign up to set email alerts
|

A comparative analysis of tissue gene expression data from high-throughput studies

Abstract: High-throughput technologies were employed over the past decade to study the expression profiles of cells and tissues. There are large collections of accumulated data from public databases and numerous research articles were published on these data. In the current study, we performed meta-analysis on the gene expression data from human liver and kidney tissues produced from five different technologies: EST, SAGE, MPSS, microarray, and RNA-Seq. We found RNA-Seq was the most sensitive in the number of genes it d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…The limited data hamper the research of active ingredients biosynthetic and metabolic mechanisms in A. mongolicus . In recent years, RNA-seq is quickly developed as a massively parallel sequencing method to generate transcriptome profiles at large scale and relatively low cost[ 20 , 21 ]. Since RNA-seq is not restricted to detecting transcripts of known genes, it is particularly useful for non-model organisms with no available genomic data[ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The limited data hamper the research of active ingredients biosynthetic and metabolic mechanisms in A. mongolicus . In recent years, RNA-seq is quickly developed as a massively parallel sequencing method to generate transcriptome profiles at large scale and relatively low cost[ 20 , 21 ]. Since RNA-seq is not restricted to detecting transcripts of known genes, it is particularly useful for non-model organisms with no available genomic data[ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our approach differed form that in a recent study (Ma et al, 2020) which identified 3812 candidate TSGs using expressed sequence tags (ESTs) but did not further verify for their protein‐coding potential. ESTs do not cover the transcriptome as well as RNA‐seq data (Lowe et al, 2017; Ping et al, 2012), especially for lineage‐specific genes, which are often expressed at low levels or only under specific conditions. Furthermore, in contrast to Ma et al (2020), we considered it crucial to include TE‐derived TSGs, because studies in primates and rice have shown that over 50% of lineage‐specific genes have homology to TEs (Jin et al, 2019; Toll‐Riera et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Our approach differed form that in a recent study (Ma et al, 2020) which identified 3812 candidate TSGs using expressed sequence tags (ESTs) but did not further verify for their protein-coding potential. ESTs do not cover the transcriptome as well as RNA-seq data (Lowe et al, 2017;Ping et al, 2012), especially for lineage-specific genes, which are often expressed at low levels or only under specific conditions. Furthermore, in contrast to Ma et al…”
Section: Discussionmentioning
confidence: 99%
“…Our approach differed form that in a recent study (Ma et al .,2020) which identified 3,812 candidate TSGs using expressed sequence tags (ESTs), but did not further verify for their protein-coding potential. ESTs do not cover the transcriptome as well as RNA-seq data (Ping et al ., 2012; Lowe et al ., 2017), especially for lineage-specific genes, which are often expressed at low levels or only under specific conditions. Furthermore, in contrast to Ma et al .…”
Section: Discussionmentioning
confidence: 99%
“…for their protein-coding potential. ESTs do not cover the transcriptome as well as RNA-seq data (Ping et al, 2012;Lowe et al, 2017), especially for lineage-specific genes, which are often expressed at low levels or only under specific conditions. Furthermore, in contrast to Ma et al (2020), we considered it crucial to include TE-derived TSGs, because studies in primates and rice have shown that over 50% of lineage-specific genes have homology to TEs (Toll-Riera et al, 2009;Jin et al, 2019).…”
Section: Discussionmentioning
confidence: 99%